Theatre-in-education: Confucian learning experiences of props managers in Peking Opera - Yu Dai; Azrul Azizi Amirrul; Jian Yang; Kang Xiao; Xin-Wei Li (Cogent Arts & Humanities)
The Confucian educational impact of Peking Opera has garnered considerable attention, primarily focusing on the educational experience of audiences, with limited attention to the participants. Theatre in Education (TIE) reminds us that theatre participants get a more profound educational experience. To address this gap, this study explores the Confucian educational experiences of Jianchang (props managers) participating in Peking Opera. A case study at the Peking Opera Protection and Inheritance Centre in Hunan (POPIC) applies Schechner’s performance studies theory. The results indicate that Jianchang deeply experiences the Confucian concepts of ’SanGangWuChang’ during their participation process and further internalizes them into their behaviour, such as ‘maintaining strict hierarchical order’ and ‘adhering to rigorous personal moral standards’. This research has multidisciplinary significance as it enhances the value of Peking Opera education, expands the scope of TIE, and inspires the living conservation of traditional culture. It encourages future research to explore the educational experiences of traditional theatre participants, who are an overlooked group.